The Effects of Peruvian maca (Lepidium meyenii) Root Extract on In Vitro Cultured Porcine Fibroblasts and Adipocytes - Weronika Loba-Pasternak; Mehmet Onur Aksoy; Kinga Stuper-Szablewska; Lidia Szwajkowska-Michalek; Pawel Kolodziejski; Izabela Szczerbal; Joanna Nowacka-Woszuk (Molecules)
Peruvian maca (Lepidium meyenii) is a plant known for its nutritional and medicinal properties whose use as a supplement in animal diets has attracted much interest. We studied the effects of powdered maca root extract on the growth potential of in vitro cultured porcine cells prior to its use as an additive in animal nutrition. Fibroblast cell viability (MTT), cell proliferation (BrdU), and apoptosis level (TUNEL) were measured for a range of extract doses (0, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 7.0, and 10 mg/mL). Transcript levels of CCND1, MCM2, and PCNA genes as molecular markers of cell proliferation were also determined. Next, the effects of maca extract at 2 and 5 mg/mL on in vitro induced adipogenesis were evaluated over eight days of differentiation. The transcript levels of three adipocyte marker genes (CEBPA, PPARG, and FABPB4) were measured at days 0, 4, and 8 of adipose differentiation, and lipid droplet accumulation (BODIPY staining) was also noted. No cytotoxic effect was detected on fibroblast cell viability, and the inhibitory concentration (IC50) value was determined to be IC50 > 10 mg/mL. Doses of maca extract above 3 mg/mL decreased cell proliferation. The transcript level decreased in concentrations above 5 for the MCM2 and PCNA genes. For the CCND1 gene, the transcript level decreased when the greatest maca dose was used. In the in vitro adipogenesis experiment, it was found that the rate of lipid droplet formation increased on day 4 of differentiation for both doses, while decreased lipid droplet formation was observed on day 8 for 5 mg/mL of maca extract. Significant changes were seen in the mRNA level for CEBPA and PPARG on days 4 and 8, while the transcript of FABP4 increased only on day 8 at 2 mg/mL dose. It can be concluded that the addition of Peruvian maca in small doses (<3 mg/mL) has no negative effect on porcine fibroblast growth or proliferation, while 2 mg/mL of maca extract enhances adipocyte differentiation.